2020
DOI: 10.3390/pr8111450
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Piperine Ternary Inclusion Complex Using β CD and HPMC: Physicochemical Characterization, Molecular Docking, and Antimicrobial Testing

Abstract: The present study was designed to evaluate the effect of hydroxyl propyl methyl cellulose (HPMC) on the complexation efficiency and dissolution of piperine (PPR) and β cyclodextrin (β CD) complex. The binary and ternary inclusion complexes were prepared using solvent evaporation and microwave irradiation methods. The samples were further evaluated for physicochemical evaluation, morphology, antimicrobial, and antioxidant activities. The binary and ternary samples showed high stability constant (Ks) value and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…The prepared LT-NVoptG was evaluated for antibacterial activity and results were compared with pure LT. The study was performed using the microdilution test with a slightly modified reported method [37]. The samples were tested against the microorganisms S. Aureus, E. coli and B. subtilis.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The prepared LT-NVoptG was evaluated for antibacterial activity and results were compared with pure LT. The study was performed using the microdilution test with a slightly modified reported method [37]. The samples were tested against the microorganisms S. Aureus, E. coli and B. subtilis.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Piperine is conventionally used in treatment of various gastrointestinal upsets, as well as for neurological and broncho-pulmonary disorders (asthma and chronic bronchitis)(Stojanović-Radić et al, 2019 ). Piperine encompasses wide spectrum of physiological activities including antioxidant, antimicrobial (Alshehri et al, 2020 ), anti-asthmatic, antitumor, and especially vigorous anti-inflammatory role, hence, it can be reclaimed for suppression of MERS and COVID-19 induced hyper inflammation (Damanhouri, 2014 ; Mrityunjaya et al, 2020 ). Unfortunately, its clinical applications are impeded by its hydrophobicity and low stability and rapid metabolism, hence, poor bioavailability (Ding et al, 2018 ; Imam et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used as a food supplement but also has many therapeutic properties in different diseases. Its therapeutic efficacy has been reported against diseases such as inflammation, obesity, CNS diseases and neurodegeneration protection [ 1 , 2 ]. The use of PPN has also been reported in different types of cancer.…”
Section: Introductionmentioning
confidence: 99%